2009
DOI: 10.1158/1078-0432.ccr-08-3336
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Screening for Genes Silenced by DNA Methylation Revealed an Association between RASD1 Inactivation and Dexamethasone Resistance in Multiple Myeloma

Abstract: Purpose: Epigenetic changes such as DNA methylation play a key role in the development and progression of multiple myeloma. Our aim in the present study was to use genomic screening to identify genes targeted for epigenetic inactivation in multiple myeloma and assess their role in the development of resistance to dexamethasone. Experimental Design: Gene expression was examined using microarray screening, reverse transcription-PCR, and real-time quantitative PCR. DNA methylation was examined using bisulfite PCR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 43 publications
4
44
1
Order By: Relevance
“…Several studies have reported hypermethylation in MM for specific genes, including SPARC, BNIP3, and TGFBR2 (5,20). Other genes with reported hypermethylation in MM are VHL, XAF1, EGLN1, EGLN3, CDKN2A, CCND2, TP53, DCC ESR1, CDH1, and CDKN2B, among others (6,19,24,25,27,(33)(34)(35)(36)(37). A number of reasons might explain the discordance in ours versus these other studies.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Several studies have reported hypermethylation in MM for specific genes, including SPARC, BNIP3, and TGFBR2 (5,20). Other genes with reported hypermethylation in MM are VHL, XAF1, EGLN1, EGLN3, CDKN2A, CCND2, TP53, DCC ESR1, CDH1, and CDKN2B, among others (6,19,24,25,27,(33)(34)(35)(36)(37). A number of reasons might explain the discordance in ours versus these other studies.…”
Section: Discussionmentioning
confidence: 51%
“…One of the most widely studied and understood epigenetic modifications involves methylation of CpG dinucleotides. Relatively little is still known about the degree to which CpG methylation contributes to myelomagenesis, and to date most studies have focused on the analyses of single genes (6,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Thus, the goal of this study is to perform a DNA methylation profiling analysis comparing CD138 + sorted MM and its precursor stages, MGUS and SMM, to NPC to identify important DNA methylation events associated with each tumor stage and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of GB on EPCs proliferation was determined by 2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfo-phenyl) -2H-tetrazolium, monosodium salt (WST-8) assay kit (CCK-8, Dojindo, Rockville, MD, USA) (Nojima et al, 2009). After cultivation for 7 d, adherent cells were detached with 0.25% trypsin and cultured with non-FBS EBM-2 in 96-well culture plates at 8×10 3 cells per well for 24 h. Then, the medium was replaced by fresh non-FBS EBM-2 with different concentrations of GB (0, 1.25, 5, 20, 80 and 160 μg/mL) for different periods.…”
Section: Epcs Proliferation Assaymentioning
confidence: 99%
“…EPCs are a type of cell population that have the capacity to circulate, proliferate and differentiate into mature endothelial cells, but have not yet acquired characteristic mature endothelial cell markers and have not yet formed a lumen (Asahara et al, 1997;Peichev et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to lMiDs involves mostly mutations or downregulation of cereblon expression. 47,137 Various mechanisms have been described for dexamethasone resistance: expression of a truncated glucocorticoid receptor, 138 mutations in receptor gene, 47 epigenetic silencing of RASD1, cell growth inhibitor induced by dexamethasone treatment, 139 overexpression of Hsp27, 140 or change in the secretion of cytokines and chemokines in the microenvironment. 141 Overexpression of Bruton tyrosine kinase could also play a role in resistance according to a recent study.…”
mentioning
confidence: 99%